Identification of key candidate genes and pathways in rheumatoid arthritis and osteoarthritis by integrated bioinformatical analysis - Huang, Huijing; Dong, Xinyi; Mao, Kaimin; Pan, Wanwan; Nie, Bin’en; Jiang, Lindi (Frontiers in Genetics, 2023)
Rheumatoid arthritis (RA) and osteoarthritis (OA) are most common joint disorders. Although they have showed the analogous clinical manifestations, the pathogenesis of RA and OA are different. In this study, we used the online Gene Expression Omnibus (GEO) microarray expression profiling dataset GSE153015 to identify gene signatures between RA and OA joints. The relevant data on 8 subjects which obtained from large joints of RA patients (RA-LJ), 8 subjects which obtained from small joints of RA patients (RA-SJ) and 4 subjects with OA was investigated. Differentially expressed genes (DEGs) were screened. Functional enrichment analysis of DEGs including the Gene Ontology terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were identified. Besides, protein-protein interaction (PPI) network analysis was performed, and key modules were identified. Hub genes of RA-LJ and OA group were screened, they were CD8A, GZMB, CCL5, CD2 and CXCL9, whereas CD8A, CD2, IL7R, CD27 and GZMB were hub genes of RA-SJ and OA group. What’s more, the protein expression of CD8A, CD2 and GZMB were determined by immunohistochemistry in RA and OA joint biopsies, for the sake of validating the results. The novel DEGs and functional pathways between RA and OA identified in this study may provide new insight into the underlying molecular mechanisms and therapeutic strategies of RA and OA.